Preparation method of composite calcium ferrite

By calcining titanium gypsum and industrial green alum to form composite calcium ferrite, the problems of resource waste and environmental pollution in the titanium dioxide production process are solved, and the resource utilization and efficient desulfurization effect of titanium gypsum and industrial green alum are achieved.

CN119306257APending Publication Date: 2025-01-14PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411467106.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Titanium gypsum and industrial green alum produced in the titanium dioxide production process have not been effectively utilized, resulting in waste of resources and environmental pollution. Its treatment costs are high and its application scope is narrow, which limits the company's green development and environmental protection requirements.

Method used

By mixing the pretreated titanium gypsum with industrial green alum, mixing it with water, pressing it into blocks and then calcining it to produce compound calcium ferrite, thereby realizing calcium, sulfur, iron and other elements in titanium gypsum and industrial green alum. comprehensive resource utilization.

Benefits of technology

The resource utilization of titanium gypsum and industrial green alum has been realized, the utilization rate and environmental friendliness of resources have been improved, the treatment cost has been reduced, and sulfur dioxide has been generated through high-temperature decomposition to recover sulfuric acid, improving the overall desulfurization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306257A_ABST
    Figure CN119306257A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metallurgy, in particular to a preparation method of composite calcium ferrite, which comprises the following steps: mixing and grinding pretreated industrial copperas and pretreated titanium gypsum to obtain a mixture, or mixing and grinding dried industrial copperas and pretreated titanium gypsum to obtain a mixture; mixing the mixture with water, pressing the mixture into blocks, and drying the blocks to obtain a blocky mixture; and calcining the blocky mixture to obtain the composite calcium ferrite. The titanium gypsum is rich in calcium, sulfur and a part of iron, the industrial copperas are mainly ferrous sulfate, the two solid wastes are mixed and calcined, the mixture is decomposed to generate sulfur dioxide and can be recycled to prepare sulfuric acid, calcium and iron are combined to form composite calcium ferrite, valuable elements such as calcium, sulfur and iron in the titanium gypsum and the industrial copperas can be fully utilized, and the industrial copperas can be recycled. And resource comprehensive utilization of typical solid wastes in the titanium dioxide production industry is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a method for preparing composite calcium ferrite. Background Art

[0002] Due to its resource characteristics, the production of titanium dioxide in Panxi region of my country mainly adopts the sulfuric acid method titanium dioxide process. This process has the advantages of low cost, mature technology and low raw material requirements. However, the problems of large by-product output, low added value and environmental pollution are also its shortcomings that cannot be ignored, which greatly restricts the green development of enterprises. At present, titanium dioxide enterprises produce about 3 tons of industrial green vitriol and 4 tons of titanium gypsum for every ton of titanium dioxide produced. Taking Panzhihua Iron and Steel as an example, the annual output of titanium gypsum exceeds 800,000 tons and the output of industrial green vitriol exceeds 660,000 tons. At present, except for a small part of titanium gypsum used in the cement industry after drying, most of it is stored, resulting in a great waste of resources such as calcium, iron and sulfur, and bringing environmental pollution risks. Titanium gypsum has high processing costs, narrow application range and difficulty in large-scale consumption due to its iron content. Long-term storage also causes a large economic burden and environmental risks to enterprises. The utilization of industrial green vitriol is also relatively limited. Although there are some utilization methods, such as preparing iron red and producing food-grade feed additives, these utilization methods have not been widely used due to cost, market demand and other reasons. Most of the green vitriol is still stored or sold at a subsidized cost, failing to effectively realize resource utilization.

[0003] In recent years, with the continuous tightening of environmental protection policies at all levels, titanium dioxide companies will face heavy environmental pressure. Therefore, how to achieve the comprehensive resource utilization of typical solid waste in the titanium dioxide production industry has become an imminent issue. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing composite calcium ferrite, which can realize the comprehensive resource utilization of typical solid waste in the titanium dioxide production industry and make full use of valuable elements such as calcium, sulfur, and iron in titanium gypsum and industrial green vitriol.

[0005] The present invention provides a method for preparing composite calcium ferrite, comprising the following steps:

[0006] A1) mixing and grinding pretreated industrial green vitriol and pretreated titanium gypsum to obtain a mixture H1;

[0007] A2) mixing the mixed material H1 with water, pressing into blocks, and drying to obtain a block mixed material K1;

[0008] A3) calcining the block mixture K1 to obtain composite calcium ferrite;

[0009] or

[0010] B1) drying industrial green vitriol, mixing and grinding with pretreated titanium gypsum to obtain a mixture H2;

[0011] B2) mixing the mixture H2 with water, pressing into blocks, and drying to obtain a block mixture K2;

[0012] B3) calcining the block mixture K2 to obtain composite calcium ferrite;

[0013] The pretreated titanium gypsum is prepared by preparing a block mixture G1 from raw materials including titanium gypsum, a reducing agent and water, and then calcining it;

[0014] The pretreated industrial green vitriol is prepared by calcining a block mixture G2 made from raw materials including industrial green vitriol, water and a binder.

[0015] Preferably, the method for preparing the pretreated titanium gypsum comprises the following steps:

[0016] a1) drying the titanium gypsum, mixing it with a reducing agent and grinding it to obtain a mixture S1;

[0017] a2) mixing the mixed material S1 with water, pressing into blocks, and drying to obtain a block mixed material G1;

[0018] a3) calcining the block mixture G1 to obtain pretreated titanium gypsum.

[0019] Preferably, in step a1), the amount of the reducing agent added is 1% to 10% of the total mass of the dried titanium gypsum;

[0020] In step a2), the amount of water added is 5% to 10% of the mass of the mixture S1;

[0021] In step a3), the calcination temperature is 1000-1300° C. and the calcination time is 0.5-2 h.

[0022] Preferably, the preparation method of the pretreated industrial green vitriol comprises the following steps:

[0023] b1) drying the industrial green vitriol and grinding it to obtain a mixture S2;

[0024] b2) mixing the mixture S2 with water and a binder, pressing the mixture into a block, and drying the block mixture G2;

[0025] b3) calcining the block mixture G2 to obtain pretreated industrial green vitriol.

[0026] Preferably, in step b2), the binder comprises methyl cellulose, water glass or starch;

[0027] The amount of the binder added is 1% to 3% of the mass of the mixture S2;

[0028] The amount of water added is 5% to 10% of the mass of the mixed material S2.

[0029] Preferably, in step b3), the calcination temperature is 800-1000° C. and the calcination time is 0.5-2 h.

[0030] Preferably, in step A1), the mass ratio of the pretreated industrial green vitriol to the pretreated titanium gypsum is 1.2 to 2:1;

[0031] In step A2), the amount of water added is 5% to 10% of the mass of the mixture H1.

[0032] Preferably, in step A3), the calcination temperature is 1100-1300° C. and the calcination time is 0.5-2 h.

[0033] Preferably, in step B1), the mass ratio of the dried industrial green vitriol to the pretreated titanium gypsum is 0.2 to 0.5:1;

[0034] In step B2), the amount of water added is 5% to 10% of the mass of the mixed material H2.

[0035] Preferably, in step B3), the calcination temperature is 1100-1300° C. and the calcination time is 0.5-2 h.

[0036] The invention provides a preparation method of composite calcium ferrite, comprising the following steps: A1) mixing and grinding pretreated industrial green vitriol and pretreated titanium gypsum to obtain a mixture H1; A2) mixing the mixture H1 with water, pressing it into a block, and drying it to obtain a block mixture K1; A3) calcining the block mixture K1 to obtain composite calcium ferrite; or B1) drying industrial green vitriol, mixing and grinding it with pretreated titanium gypsum to obtain a mixture H2; B2) mixing the mixture H2 with water, pressing it into a block, and drying it to obtain a block mixture K2; B3) calcining the block mixture K2 to obtain composite calcium ferrite; the pretreated titanium gypsum is obtained by calcining a block mixture G1 prepared from raw materials including titanium gypsum, a reducing agent and water; the pretreated industrial green vitriol is obtained by calcining a block mixture G2 prepared from raw materials including industrial green vitriol, water and a binder. Titanium gypsum is rich in calcium, sulfur, and some iron, and industrial green vitriol is mainly ferrous sulfate. The present invention mixes the above two solid wastes and calcines them to decompose them to produce sulfur dioxide, which can be recycled to produce sulfuric acid. Calcium combines with iron to form composite calcium ferrite, which can make full use of valuable elements such as calcium, sulfur, and iron in titanium gypsum and industrial green vitriol, thereby realizing the comprehensive resource utilization of typical solid wastes in the titanium dioxide production industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A flow chart of the preparation process of composite calcium ferrite provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The present invention provides a method for preparing composite calcium ferrite, comprising the following steps:

[0040] A1) mixing and grinding pretreated industrial green vitriol and pretreated titanium gypsum to obtain a mixture H1;

[0041] A2) mixing the mixed material H1 with water, pressing into blocks, and drying to obtain a block mixed material K1;

[0042] A3) calcining the block mixture K1 to obtain composite calcium ferrite;

[0043] or

[0044] B1) drying industrial green vitriol, mixing and grinding with pretreated titanium gypsum to obtain a mixture H2;

[0045] B2) mixing the mixture H2 with water, pressing into blocks, and drying to obtain a block mixture K2;

[0046] B3) calcining the block mixture K2 to obtain composite calcium ferrite;

[0047] The pretreated titanium gypsum is prepared by preparing a block mixture G1 from raw materials including titanium gypsum, a reducing agent and water, and then calcining it;

[0048] The pretreated industrial green vitriol is prepared by calcining a block mixture G2 made from raw materials including industrial green vitriol, water and a binder.

[0049] Figure 1 A flow chart of the preparation process of composite calcium ferrite provided in an embodiment of the present invention.

[0050] In certain embodiments of the present invention, the method for preparing the pretreated titanium gypsum comprises the following steps:

[0051] a1) drying the titanium gypsum, mixing it with a reducing agent and grinding it to obtain a mixture S1;

[0052] a2) mixing the mixed material S1 with water, pressing into blocks, and drying to obtain a block mixed material G1;

[0053] a3) calcining the block mixture G1 to obtain pretreated titanium gypsum.

[0054] In step a1):

[0055] The titanium gypsum is dried, mixed with a reducing agent and ground to obtain a mixture S1.

[0056] In certain embodiments of the present invention, the titanium gypsum is a by-product gypsum of titanium dioxide produced by the sulfuric acid process. The main components of the dried titanium gypsum include CaSO4, Fe2O3, TiO2 and SiO2. The present invention calculates the content of CaSO4 by measuring the content of CaO and SO3. In the titanium gypsum, the content of CaO is 26wt% to 32wt%, the content of SO3 is 33wt% to 44wt%, the content of Fe2O3 is 5wt% to 12wt%, the content of TiO2 is 1wt% to 5wt%, and the content of SiO2 is 1wt% to 5wt%. Specifically, the content of CaO is 29.2wt%, the content of SO3 is 35.4wt%, the content of Fe2O3 is 9.5wt%, the content of TiO2 is 3.3wt%, and the content of SiO2 is 2.8wt%.

[0057] The drying temperature is 120-150° C., such as 150° C.; the titanium gypsum after drying is composite titanium gypsum; and the composite titanium gypsum includes hemihydrate gypsum and / or anhydrous gypsum.

[0058] The reducing agent includes coal powder or coke powder; the fixed carbon content (mass content) of the reducing agent is greater than 75%, such as 79.8%; the amount of the reducing agent added is 1% to 10% of the total mass of the dried titanium gypsum; such as 1%, 3%, 4%, 5% or 9%. The reducing agent mainly decomposes CaSO4 and uses C to remove oxygen from S. The reaction formula is shown in formula (1):

[0059] (2CaSO4+C=2CaO+2SO2+CO2) Formula (1).

[0060] At the same time, the addition of C can reduce the decomposition temperature of CaSO4 by 825℃.

[0061] The grinding is carried out in a ball mill. The particle size of the mixed material S1 after grinding is below 200 meshes.

[0062] In step a2):

[0063] The mixed material S1 is mixed with water, pressed into blocks, and dried to obtain a block mixed material G1.

[0064] In certain embodiments of the present invention, the amount of water added is 5% to 10% of the mass of the mixture S1; for example, 8%.

[0065] In certain embodiments of the present invention, the material is pressed into a block having a size of 1 to 3 cm, such as a cylindrical shape.

[0066] The drying temperature is 80-120° C., such as 100° C., and the drying time is 1-2 hours, such as 1.5 hours.

[0067] In step a3):

[0068] The block mixture G1 is calcined to obtain pretreated titanium gypsum.

[0069] In certain embodiments of the present invention, the calcination temperature is 1000-1300°C, such as 1100°C, 1200°C or 1300°C; the time is 0.5-2h, such as 0.5h, 1h, 1.5h or 2h. During the calcination, the reactor is in a negative pressure state, and the present application has no special restrictions on the specific negative pressure value, such as 0.95 atmospheres. The calcination is carried out in an atmosphere furnace.

[0070] During the calcination process, sulfur-rich flue gas is generated. In certain embodiments of the present invention, the sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid. The sulfuric acid can be prepared by a contact method.

[0071] In certain embodiments of the present invention, after the calcination, the process further comprises: cooling to obtain pretreated titanium gypsum. The cooling is natural cooling to room temperature.

[0072] In certain embodiments of the present invention, the main components of the pretreated titanium gypsum include 44 wt% to 65 wt% CaO, 10 wt% to 20 wt% Fe2O3, and 4 wt% to 15 wt% SiO2. Specifically, the content of CaO is 44.8 wt%, the content of Fe2O3 is 14.2 wt%, and the content of SiO2 is 4.1 wt%.

[0073] In certain embodiments of the present invention, the method for preparing the pretreated industrial green vitriol comprises the following steps:

[0074] b1) drying the industrial green vitriol and grinding it to obtain a mixture S2;

[0075] b2) mixing the mixture S2 with water and a binder, pressing the mixture into a block, and drying the block mixture G2;

[0076] b3) calcining the block mixture G2 to obtain pretreated industrial green vitriol.

[0077] In step b1):

[0078] The industrial green vitriol is dried and then ground to obtain a mixture S2.

[0079] In certain embodiments of the present invention, the industrial green vitriol is a byproduct of titanium dioxide produced by the sulfuric acid process. The main components of the dried industrial green vitriol include TFe (total iron content) 20wt% to 35wt%, TS (total sulfur content) 8wt% to 20wt%, MgO 1wt% to 3wt%, Al2O3 0wt% to 1wt%, TiO2 0 wt% to 1wt%, SiO2 0 wt% to 1wt%, and MnO 0.2wt% to 2wt%. Specifically, the industrial green vitriol includes: TFe (total iron content) 28.3wt%, TS (total sulfur content) 18.92wt%, MgO 2.6wt%, Al2O3 0.41wt%, TiO2 0.52wt%, SiO2 0.5wt%, and MnO 1.53wt%.

[0080] The drying temperature is 120-150° C., such as 150° C.; the industrial green vitriol after drying is composite ferrous sulfate; the composite ferrous sulfate includes ferrous sulfate monohydrate and / or ferrous sulfate dihydrate.

[0081] The grinding is carried out in a ball mill. The particle size of the mixed material S2 after the grinding is below 200 meshes.

[0082] In step b2):

[0083] The mixed material S2 is mixed with water and a binder, pressed into blocks, and dried to form a block mixed material G2.

[0084] In some embodiments of the present invention, the binder includes methyl cellulose, water glass or starch. The amount of the binder added is 1% to 3% of the mass of the mixture S2; for example, 2%. The amount of water added is 5% to 10% of the mass of the mixture S2; for example, 8%.

[0085] In certain embodiments of the present invention, the material is pressed into a block having a size of 1 to 3 cm, such as a cylindrical shape.

[0086] The drying temperature is 80-120° C., such as 100° C., and the drying time is 1-2 hours, such as 1.5 hours.

[0087] In step b3):

[0088] The block mixture G2 is calcined to obtain pretreated industrial green vitriol.

[0089] In certain embodiments of the present invention, the calcination temperature is 800-1000°C, such as 800°C, 900°C, 1000°C; the time is 0.5-2h, such as 0.5h, 1.5h, 2h. During the calcination, the reactor is in a negative pressure state, and the present application has no special restrictions on the specific negative pressure value, such as 0.95 atmospheres. The calcination is carried out in an atmosphere furnace.

[0090] During the calcination process, sulfur-rich flue gas is generated. In certain embodiments of the present invention, the sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid. The sulfuric acid can be prepared by a contact method.

[0091] In certain embodiments of the present invention, after the calcination, the process further comprises: cooling to obtain pretreated industrial green vitriol, wherein the cooling is natural cooling to room temperature.

[0092] In certain embodiments of the present invention, the main component of the pretreated industrial green vitriol is Fe2O3, with a mass content of 85% to 95%, such as 89.1%.

[0093] The first option:

[0094] In step A1):

[0095] The pretreated industrial green vitriol and the pretreated titanium gypsum are mixed and ground to obtain a mixture H1.

[0096] In certain embodiments of the present invention, the mass ratio of the pretreated industrial green vitriol to the pretreated titanium gypsum is 1.2 to 2:1, such as 1.2:1, 1.5:1, 1.6:1, 1.7:1, and 1.9:1.

[0097] The grinding is carried out in a ball mill. The particle size of the mixed material H1 after grinding is below 200 meshes.

[0098] In step A2):

[0099] The mixed material H1 is mixed with water, pressed into blocks, and dried to obtain a block mixed material K1.

[0100] In certain embodiments of the present invention, the amount of water added is 5% to 10% of the mass of the mixture H1, such as 8%.

[0101] In certain embodiments of the present invention, the material is pressed into a block having a size of 1 to 3 cm, such as a cylindrical shape.

[0102] The drying temperature is 80-120° C., such as 100° C., and the drying time is 1-2 hours, such as 1.5 hours.

[0103] In step A3):

[0104] The block mixture K1 is calcined to obtain composite calcium ferrite.

[0105] In certain embodiments of the present invention, the calcination temperature is 1100-1300°C, such as 1100°C, 1200°C, 1300°C; the time is 0.5-2h, such as 0.5h, 1h or 2h. During the calcination, the reactor is in a negative pressure state, and the present application has no special restrictions on the specific negative pressure value, such as 0.95 atmospheres. The calcination is carried out in an atmosphere furnace.

[0106] During the calcination process, sulfur-rich flue gas is generated. In certain embodiments of the present invention, the sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid. The sulfuric acid can be prepared by a contact method.

[0107] In certain embodiments of the present invention, after the calcination, the process further comprises: cooling to obtain composite calcium ferrite. The cooling is natural cooling to room temperature.

[0108] Second option:

[0109] In step B1):

[0110] The industrial green vitriol is dried and then mixed and ground with the pretreated titanium gypsum to obtain a mixture H2.

[0111] In certain embodiments of the present invention, the mass ratio of the dried industrial green vitriol to the pretreated titanium gypsum is 0.2-0.5:1, such as 0.2:1, 0.3:1, 0.4:1, 0.5:1.

[0112] The grinding is carried out in a ball mill. The particle size of the mixed material H2 after the grinding is below 200 meshes.

[0113] In step B2):

[0114] The mixed material H2 is mixed with water, pressed into blocks, and dried to obtain a block mixed material K2.

[0115] In certain embodiments of the present invention, the amount of water added is 5% to 10% of the mass of the mixed material H2.

[0116] In certain embodiments of the present invention, the material is pressed into a block having a size of 1 to 3 cm, such as a cylindrical shape.

[0117] The drying temperature is 80-120° C., such as 100° C., and the drying time is 1-2 hours, such as 1.5 hours.

[0118] In step B3):

[0119] The block mixture K2 is calcined to obtain composite calcium ferrite.

[0120] In certain embodiments of the present invention, the calcination temperature is 1100-1300°C, such as 1100°C, 1200°C, 1300°C; the time is 0.5-2h, such as 1h, 1.5h, 2h. During the calcination, the reactor is in a negative pressure state, and the application has no special restrictions on the specific negative pressure value, such as 0.95 atmospheres. The calcination is carried out in an atmosphere furnace.

[0121] During the calcination process, sulfur-rich flue gas is generated. In certain embodiments of the present invention, the sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid. The sulfuric acid can be prepared by a contact method.

[0122] In certain embodiments of the present invention, after the calcination, the process further comprises: cooling to obtain composite calcium ferrite. The cooling is natural cooling to room temperature.

[0123] The principle of the present invention is:

[0124] Titanium gypsum can reduce the decomposition temperature under reducing conditions, and its main substances after high-temperature decomposition are calcium oxide and sulfur dioxide. Industrial green vitriol decomposes into ferric oxide and sulfur dioxide at high temperatures. The calcium oxide generated after the decomposition of titanium gypsum directly reacts with industrial green vitriol, or the calcium oxide generated after the decomposition reacts with ferric oxide generated after the decomposition of industrial green vitriol, both of which will generate calcium ferrite through the occurrence of solid solution reaction.

[0125] The beneficial effects are:

[0126] The present invention decomposes titanium gypsum at high temperature by externally adding carbon, so that sulfur is removed in the form of sulfur dioxide, and the decomposed product is mainly calcium oxide. The reaction of industrial green vitriol and the decomposed titanium gypsum in an oxidizing atmosphere is more conducive to the decomposition of green vitriol, improves the proportion and quality of the generated composite calcium ferrite, further improves the overall desulfurization efficiency, and the desulfurization rate reaches more than 97%. The calcium ferrite with an effective content of more than 60% is obtained, so that the calcium, sulfur and iron resources in titanium gypsum and industrial green vitriol can be fully utilized.

[0127] The present invention allows various materials to be fully mixed and contacted by means of ball milling and briquetting, which is beneficial to the full contact of solid phase reactants, thereby reducing the calcination temperature and improving the conversion rate.

[0128] In order to further illustrate the present invention, a preparation method of a composite calcium ferrite provided by the present invention is described in detail below in conjunction with examples, but it should not be understood as limiting the scope of protection of the present invention.

[0129] Example

[0130] The titanium gypsum and industrial green vitriol used in the examples were both obtained from a chemical enterprise. After being dried at 150° C., their main chemical compositions were measured and shown in Tables 1 and 2.

[0131] Table 1 Main components of dried titanium gypsum

[0132]

[0133] Table 2 Main components of industrial green vitriol after drying

[0134]

[0135] Preparation of pretreated titanium gypsum:

[0136] 1-1) The dried titanium gypsum and a reducing agent (coal powder, with a fixed carbon content (mass content) of 79.8%) are mixed and ground in a ball mill to obtain a mixture S1 with a particle size of less than 200 meshes; the amount of the reducing agent added accounts for n% of the total mass of the dried titanium gypsum;

[0137] 1-2) Mixing the mixture S1 with water (the amount of water added is 8% of the mass of the mixture S1), pressing into a cylindrical shape with a size of 1 to 3 cm, and drying at 100° C. for 1.5 h to obtain a block mixture G1;

[0138] 1-3) placing the block mixture G1 in a reactor (atmosphere furnace) for calcination (calcination temperature is denoted as T1, time is denoted as t1); during the calcination, the reactor is in a negative pressure state, such as 0.95 atmospheres; after naturally cooling to room temperature, pretreated titanium gypsum is obtained; the main components of the pretreated titanium gypsum include CaO 44.8wt%, Fe2O314.2wt%, and SiO24.1wt%.

[0139] The sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid.

[0140] Preparation of pretreated industrial green vitriol:

[0141] 2-1) grinding the dried industrial green vitriol in a ball mill to obtain a mixture S2 with a particle size of less than 200 meshes;

[0142] 2-2) Mix the mixture S2 with water (the amount of water added is 8% of the mass of the mixture S2) and a binder (methyl cellulose, the amount of the binder added is 2% of the mass of the mixture S2), press into a cylindrical shape with a size of 1 to 3 cm, and dry at 100° C. for 1.5 hours to prepare a block mixture G2;

[0143] 2-3) placing the block mixture G2 in a reactor (atmosphere furnace) for calcination (calcination temperature is denoted as T2, time is denoted as t2); during the calcination, the reactor is in a negative pressure state, such as 0.95 atmospheres; after naturally cooling to room temperature, pretreated industrial green vitriol is obtained; the main component of the pretreated industrial green vitriol is Fe2O3, with a mass content of 89.1%.

[0144] The sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid.

[0145] The first option:

[0146] 3-1) Pretreated industrial green vitriol and pretreated titanium gypsum are placed in a ball mill for mixing and grinding to obtain a mixture H1 with a particle size of less than 200 meshes; the mass ratio of the pretreated industrial green vitriol to the pretreated titanium gypsum is recorded as X2 / X1;

[0147] 3-2) Mixing the mixture H1 with water (the amount of water added is 8% of the mass of the mixture H1), pressing into a cylindrical shape with a size of 1 to 3 cm, and drying at 100° C. for 1.5 h to obtain a block mixture K1;

[0148] 3-3) placing the block mixture K1 in a reactor (atmosphere furnace) for calcination (calcination temperature is recorded as T3, time is recorded as t3); during the calcination, the reactor is in a negative pressure state, such as 0.95 atmospheres; after naturally cooling to room temperature, composite calcium ferrite is obtained;

[0149] The sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid.

[0150] The process parameters involved in the first scheme and the performance parameters of the prepared composite calcium ferrite are shown in Table 3.

[0151] Table 3 Process parameters involved in the first solution and performance parameters of the prepared composite calcium ferrite

[0152]

[0153]

[0154] The results in Table 3 show that the total S removal efficiency of this method exceeds 98%, indicating that most of the S is effectively decomposed. The sulfur-rich flue gas is collected and concentrated sulfuric acid can be prepared using the existing mature process. The S content in the prepared composite calcium ferrite sample can be as low as 0.17wt%, and the purity of the composite calcium ferrite exceeds 63%, and can even reach 77.1%. The remaining material is Fe3O4, so it can fully meet the needs of composite calcium ferrite for sintering preflux.

[0155] Second option:

[0156] 4-1) placing the dried industrial green vitriol and pretreated titanium gypsum in a ball mill for mixing and grinding to obtain a mixture H2 with a particle size of less than 200 mesh; the mass ratio of the dried industrial green vitriol to the pretreated titanium gypsum is X4 / X3;

[0157] 4-2) Mixing the mixture H2 with water (the amount of water added is 8% of the mass of the mixture H1), pressing into a cylindrical shape with a size of 1 to 3 cm, and drying at 100° C. for 1.5 h to obtain a block-shaped mixture K2;

[0158] 4-3) placing the block mixture K2 in a reactor (atmosphere furnace) for calcination (calcination temperature is recorded as T4, time is recorded as t4); during the calcination, the reactor is in a negative pressure state, such as 0.95 atmospheres; after naturally cooling to room temperature, composite calcium ferrite is obtained;

[0159] The sulfur-rich flue gas generated during the calcination process is collected and used to prepare sulfuric acid.

[0160] The process parameters involved in the second scheme and the performance parameters of the prepared composite calcium ferrite are shown in Table 4.

[0161] Table 4 Process parameters involved in the second scheme and performance parameters of the prepared composite calcium ferrite

[0162]

[0163]

[0164] The results in Table 4 show that when the composite calcium ferrite sample is prepared by this route, the total S removal efficiency exceeds 98%, and this part of the flue gas can be collected and concentrated sulfuric acid can be prepared by mature technology. The S content in the prepared composite calcium ferrite sample can be as low as 0.19%, and the purity of the composite calcium ferrite exceeds 67%, and can even reach 79.5%. The remaining phase is still Fe3O4, which meets the needs of pre-fluxing composite calcium ferrite for sintering.

[0165] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing composite calcium ferrite, comprising the following steps: A1) mixing and grinding pretreated industrial green vitriol and pretreated titanium gypsum to obtain a mixture H1; A2) mixing the mixed material H1 with water, pressing into blocks, and drying to obtain a block mixed material K1; A3) calcining the block mixture K1 to obtain composite calcium ferrite; or B1) drying industrial green vitriol, mixing and grinding with pretreated titanium gypsum to obtain a mixture H2; B2) mixing the mixture H2 with water, pressing into blocks, and drying to obtain a block mixture K2; B3) calcining the block mixture K2 to obtain composite calcium ferrite; The pretreated titanium gypsum is prepared by preparing a block mixture G1 from raw materials including titanium gypsum, a reducing agent and water, and then calcining it; The pretreated industrial green vitriol is prepared by preparing a block mixture G2 from raw materials including industrial green vitriol, water and a binder, and then calcining the mixture.

2. The preparation method according to claim 1, characterized in that: The preparation method of the pretreated titanium gypsum comprises the following steps: a1) drying the titanium gypsum, mixing it with a reducing agent and grinding it to obtain a mixture S1; a2) mixing the mixed material S1 with water, pressing into blocks, and drying to obtain a block mixed material G1; a3) calcining the block mixture G1 to obtain pretreated titanium gypsum.

3. The preparation method according to claim 2, characterized in that: In step a1), the amount of the reducing agent added is 1% to 10% of the total mass of the dried titanium gypsum; In step a2), the amount of water added is 5% to 10% of the mass of the mixture S1; In step a3), the calcination temperature is 1000-1300° C. and the calcination time is 0.5-2 h.

4. The preparation method according to claim 1, characterized in that: The preparation method of the pre-treated industrial green vitriol comprises the following steps: b1) drying the industrial green vitriol and grinding it to obtain a mixture S2; b2) mixing the mixture S2 with water and a binder, pressing the mixture into a block, and drying the block mixture G2; b3) calcining the block mixture G2 to obtain pretreated industrial green vitriol.

5. The preparation method according to claim 4, characterized in that: In step b2), the binder includes methyl cellulose, water glass or starch; The amount of the binder added is 1% to 3% of the mass of the mixture S2; The amount of water added is 5% to 10% of the mass of the mixed material S2.

6. The preparation method according to claim 4, characterized in that: In step b3), the calcination temperature is 800-1000° C. and the calcination time is 0.5-2 h.

7. The preparation method according to claim 1, characterized in that: In step A1), the mass ratio of the pretreated industrial green vitriol to the pretreated titanium gypsum is 1.2 to 2:1; In step A2), the amount of water added is 5% to 10% of the mass of the mixture H1.

8. The preparation method according to claim 1, characterized in that: In step A3), the calcination temperature is 1100-1300° C. and the calcination time is 0.5-2 h.

9. The preparation method according to claim 1, characterized in that: In step B1), the mass ratio of the dried industrial green vitriol to the pretreated titanium gypsum is 0.2-0.5:1; In step B2), the amount of water added is 5% to 10% of the mass of the mixed material H2.

10. The preparation method according to claim 1, characterized in that: In step B3), the calcination temperature is 1100-1300° C. and the calcination time is 0.5-2 h.

Citation Information

Cited By

  • Method for synergistically harmlessly treating waste incineration fly ash and steelmaking furnace dust and preparing sintering-grade calcium ferrite

    CN120648921A

  • Method for preparing composite calcium ferrite through multi-source solid waste low-temperature catalysis

    CN121063588A